Limiti, confini, interfacce – Riflessioni con Pippo Gianoni - Valentini, Antonella (Ri-Vista. Research for landscape architecture, 2006)
This dialogue is the result of a virtual meeting on the theme of limits with Pippo Gianoni. These reflections are the result of an exchange of epistolary opinions - using the contemporary means of communication – suffering perhaps the freshness of a real conversation, but enjoying the possibilities to face this complex and perhaps wandering theme, through a pondered reflection on the distance between mind (the first idea of limit) and action (the registration of that idea). Pippo Gianoni answers the questions expressing some reflection on the sense of limit that come from a comprehension of the reality in which is daily tried the perception of limit, as expert in ecology and planner, based on tradition, and from a wide knowledge of culture in its different forms of expression.